AB1379 Potential diagnostic serum immunological marker panel in primary and secondary osteoarthritis in sri lankan patients. (12th June 2018) - Rankotgedera, S.; Atukorala, I.; Munidasa, D.; Wijayaratne, L.; Udagama, P.
Abstract : Background: Osteoarthritis (OA) is commonly perceived as a degenerative joint disease but it is now established that inflammation contributes to OA. ThoughOA is categorised into primary and secondary osteoarthritis, most clinicians manage patients of both categories in a similar manner. Objectives: The current study aimed to identify potential diagnostic markers of primary and secondary OA. Two cohorts of Sri Lankan patients, one with primary OA and another with secondary OA were assessed for a selected panel of immunologic mediators i.e. cytokines (TNF-α, IL-1β, IL-6, IL-10) and nitric oxide derivatives (NOx). Methods: A case control study was conducted with 40 OA patients (Primary, n=30; Secondary, n=10), and 60 age and gender matched controls (normal healthy, n=30; Systemic Lupus Erythematosus (SLE) disease control, n=30). The socioeconomic and demographic data were accrued via an interviewer administered questionnaire. Sandwich ELISAs assayed serum cytokine levels, while the 'Griess assay' measured serum NOx levels. Results: In comparison to healthy controls, OA patients showed significantly higher serum concentrations of all five analytes tested (p<0.05). Patients with primary OA had significantly higher levels of TNF-α and IL-1β and lower level of IL-6 in serum compared to disease controls (SLE) (p<0.05). secondary OA patients exhibited a significant increase in serum TNF-α and IL-1β and lower serum IL-10 levels compared to disease controls (p<0.05). In the two test groups, the serum levels of TNF-α and IL-6 were significantly elevated in secondary OA patients (p<0.05). The NOx concentrations between the two test groups was not significantly different. The Th1:Th2 cytokine ratio (TNF-α:IL-10) was significantly higher in secondary OA compared with primary OA (p<0.05). The Receiver operating characteristic (ROC) curves identified TNF-α and IL-10 as potential diagnostic biomarkers of both primary OA and secondary OA compared with healthy controls. IL1-β and IL-6 may be used specifically as diagnostic biomarkers for primary and secondary OA, respectively, when compared with healthy individuals.TNF-α is a suitable biomarker for the diagnosis of both primary and secondary OA when compared to SLE patients, whereas IL-6 and IL-1β were apparent explicit markers of primary OA, while IL-10 was exclusive for secondary OA. Conclusions: This preliminary study suggests that higher levels of inflammatory cytokines are present in secondary OA compared to primary OA. Furthermore, distinct markers for primary and secondary OA were identified, indivative of the potential for developing different therapeutic agents for the different types of OA. Acknowledgements: The authors acknowledge the University of Colombo, Sri Lanka for funding. Disclosure of Interest: None declared